(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The effect of sawdust on soil nutrients in Oju Local Government Area of Benue State was examined. Three composite soil samples of 500 g were collected each from sawdust dumpsites and adjacent normal sites in Ichakobe Ibilla using a soil auger and stored in a polyethene bag. Soil samples were air-dried and sieved. Physical, chemical and microbial characteristics soil samples were determined according to standard methods. Data were analyzed using analysis of variance (ANOVA) and a follow-up test done using Duncan Multiple Range for any significant difference. The soil colour from normal sites were reddish, reddish-yellow and brownish red while they were ash, brownish and yellowish-brown in soils from sawdust dumpsites. Pseudomonas aurogenous, and Baccilus sp were common to normal and sawdust dumpsites while Entrobacter sp and Escherichia coli were only foun4d in the normal sites and Salmonella sp was seen only in soils from the sawdust dumpsites. Yeast cells and Rhizopus sp were common to soils from normal and sawdust dumpsites while Mucor sp was specific to soils from normal sites. Aspergillus sp was found in soils from sawdust dumpsite. Nitrogen, Phosphorus, Potassium, organic matter, Organic Carbon, Water, and Cation Exchange Capacity tend to be higher in sawdust dumpsites than in the normal site. SO3, Na2O, CaO, Fe2SO4 and MnO were all higher in soils from sawdust dumpsites than soil from soils normal sites. In conclusion, soils from sawdust dumpsites had more nutrient than the normal adjacent soil and as such, it is better for the growth of